Evidence for a dysfunction and disease-promoting role of the circadian clock in the diabetic retina. (October 2021) - Vancura, Patrick; Oebel, Laura; Spohn, Simon; Frederiksen, Ute; Schäfer, Kristina; Sticht, Carsten; Spessert, Rainer
Abstract: Diabetic retinopathy is a major complication of chronic hyperglycemia and a leading cause of blindness in developed countries. In the present study the interaction between diabetes and retinal clocks was investigated in mice. It was seen that in the db/db mouse – a widely used animal model of diabetic retinopathy – clock function and circadian regulation of gene expression was disturbed in the retina. Remarkably, elimination of clock function by Bmal1 -deficiency mitigates the progression of pathophysiology of the diabetic retina. Thus high-fat diet was seen to induce histopathology and molecular markers associated with diabetic retinopathy in wild type but not in Bmal1 -deficient mice. The data of the present study suggest that Bmal1 /the retinal clock system is both, a target and an effector of diabetes mellitus in the retina and hence represents a putative therapeutic target in the pathogenesis of diabetic retinopathy. Highlights: The retinal clock system is both, a target and an effector of diabetes mellitus in the retina. Diabetes alters the rhythmic expression pattern of clock and clock controlled genes in the retina and in isolated photoreceptor cells. Loss of Bmal1 mitigates the effect of high-fat diet on molecular and morphological hallmarks of diabetic retinopathy.